Organic bromine compounds produced in sea ice in Antarctic winter - Katarina Abrahamsson (Nature Portfolio, 2018)
Short-lived natural bromocarbons, which contribute to ozone depletion in the atmosphere, are believed to be produced through light-driven processes, mainly in oceans. Here the authors present bromocarbon measurements in snow, sea ice, and air during polar winter that show an unexpected source of bromine to the polar atmosphere during periods of no sunlight.